PKM of Increasing The Community Empowerment in Green Tourism In Penglipuran Village, Susut Sub-District, Bangli Regency - I Nyoman Putu Budiartha; I Nyoman Gede Sugiartha; A.A. Sagung Laksmi Dewi; I Made Minggu Widyantara; I Wayan Gede Swecana; Hartini Sarifan; Siti Aishah; Rafizah Abu Hassan; Ni Komang Wulan Prayatni Kana; I Putu Dicky Suryantha; Putu Ayu Candradiva Saraswati (Fakultas Hukum, Universitas Warmadewa, 2023)
Green Tourism problem is the main problem in developing tourism in the rural area. The awareness of tourism actors and the community in taking part in environmental protection needs to be empowered to make sustainable tourism development. The synergy of environment-based tourism development requires special attention from the government, business actors, and the community to be able to preserve the sustainability of the existing tourism. The concept of a tourist village is a form of community-based tourism that aims to prosper the people in the area. Currently, most tourism villages in Bali Province have not succeeded in developing properly. One of the problems is that people are confused about applying environmental law to the rapid progress of tourism which requires them to be innovative in gaining profits from the existing tourism activity. The problem to be answered is Efforts to realize the development of rural tourism based on green tourism in Bali. The application of the green tourism model based on the values of the local culture ​​can be used to build the concept of sustainable rural tourism in Bali. This Community Partnership Program (referred to as PKM) main objective is to develop a green tourism model that synergizes with the local cultural value ​​of the tourism villages based on Balinese cultural environmental law to increase environmental law awareness. This also helps in increasing the trust of the tourists in tourism villages, because they are legally protected by the purchased products and finally affecting guests to buy services, as well as improving the community’s standard of living. PKM activities by increasing community empowerment are related to local cultural values ​​that have been frequently carried out. However, empowering community activities as a green tourism model to increase tourism needs to be furtherly improved. Environmental protection is an effort to take responsibility which is very difficult so it results in a real decrease of the environmental quality, as well as in the pollution case, and environmental damage. However, Green tourism, which synergizes the values ​​that develop in society in protecting and preserving the environment, is an ideal form of protecting and managing the environment wisely to realize sustainable tourism development in Bali.